Distributed Voltage Regulation for Low-Voltage and High-PV-Penetration Networks With Battery Energy Storage Systems Subject to Communication Delay - Xing, Lantao; Mishra, Yateendra; Tian, Yu-Chu; Ledwich, Gerard; Wen, Changyun; He, Wangli; Du, Wenli; Qian, Feng (IEEE transactions on control systems technology, 2022)
The increasing penetration level of photovoltaic (PV) systems in low-voltage networks causes voltage regulation issues. This brief proposes a new voltage regulation strategy utilizing distributed battery energy storage systems (BESSs) while incorporating the inevitable communication delays. The proposed strategy ensures that the voltage regulation burden is appropriately shared among all involved BESSs in the network. The effects of communication delays on the performance of the proposed strategy are analyzed and an admissible delay bound is established. Case studies are conducted to verify the effectiveness of the proposed strategy.